2004
DOI: 10.1007/s00428-004-1140-z
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological features of diagnostic and clinical relevance in autoimmune pancreatitis: a study on 53 resection specimens and 9 biopsy specimens

Abstract: Background and Aims: Autoimmune pancreatitis seems to be a disease with a heterogeneous appearance. Our intention was to establish key diagnostic criteria, define grades of severity and activity, identify features of potential subtypes and evaluate the diagnostic relevance of biopsy specimens. Methods: Histopathological criteria and clinical features were recorded in pancreatic resection specimens from 53 patients who were found to have chronic pancreatitis lacking pseudocysts, calculi, irregular duct dilatati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
463
5
24

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 611 publications
(506 citation statements)
references
References 45 publications
14
463
5
24
Order By: Relevance
“…Furthermore, autoimmune pancreatitis is a uncommon disease, the largest surgical series, a multicentric study, included only 62 autoimmune pancreatitis cases. 20 Additional studies are required to understand the natural history of this hepatobiliary disease in individuals with concurrent pancreatic disease, and in those who lack pancreatic involvement, but whose liver biopsy samples show histological or immunological features of IgG4-associated cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, autoimmune pancreatitis is a uncommon disease, the largest surgical series, a multicentric study, included only 62 autoimmune pancreatitis cases. 20 Additional studies are required to understand the natural history of this hepatobiliary disease in individuals with concurrent pancreatic disease, and in those who lack pancreatic involvement, but whose liver biopsy samples show histological or immunological features of IgG4-associated cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…At presentation, only 8 to 25% of such patients have other recognized autoimmune diseases such as Sjogren sialadenitis, inflammatory bowel disease, or sclerosing cholangitis. 13 Because of pancreatic enlargement that may be confined to the head, many patients have undergone pancreatic resection because pancreatic carcinoma was suspected. 5 Histopathological examination of resection specimens has allowed the recognition of characteristic duct-centric inflammation characterized by the presence of lymphocytes and plasma cells within the duct wall and periductal connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions (granulocytic epithelial lesions) have been likened to the crypt abscesses seen in ulcerative colitis, and are most likely to be seen in patients that also have inflammatory bowel disease. 13 The disease may be localized or less commonly diffuse within the pancreas. Part of the variability in humans is attributed to the duration and severity of the process, but it is possible that part of the variability between cases reflects involvement of distinct epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation for Steroid Therapy of Autoimmune Pancreatitis [23][24][25]. It is reported that AIP with GEL has different clinical characteristics from AIP with LPSP, such as occurrence at younger age, lack of serum IgG4 elevation and frequent complication of inflammatory bowel diseases.…”
Section: Asian Diagnostic Criteria and Hisort Criteriamentioning
confidence: 99%
“…Recently, an increasing number of case reports have been made from outside of Japan, confirming that this disease exists beyond regions and races. With accumulation of international information on AIP, it is becoming clear that there are different types resembling AIP [23][24][25]. In addition, several other diagnostic criteria of AIP were proposed from several countries such as Korea [26], the US [27] and Italy [18].…”
mentioning
confidence: 99%